La sancion de la capacidad civil plena de la mujer en los paises Del cono sur, 1945-1990: una propuesta de analisis del fenomeno legal - Giordano, Veronica (Latin American research review, 2013)
The first Civil Codes defined women as subjects of relative civil incapacity, a limitation that combined with the marital power men had within marriages. This article studies the recognition of full civil capacity for women in Uruguay (1946), Brazil (1962), Argentina (1968), and Chile (1989) as part of a complex process toward the erosion (but not dissolution) of patriarchy. The article is based on a specific methodology for the analysis of legal phenomena that sheds light on the discriminatory mechanisms. Also, it assumes a comparative historical and sociological perspective that shows the different trajectories toward reform and their common elements. It traces different trajectories by assuming that each case is unique in its internal dynamics, but it shows that it is possible to identify a single pattern of change: conservative modernization. Women were still defined as subjects of legal inferiority even when they were given the right of full civil capacity. Modernization brought many changes, but traditional forces dominated the process.